Regulation, credit risk transfer with CDS, and bank lending - Thilo Pausch; Peter Welzel (Deutsche Bundesbank, 2012)
We integrate Basel II (and III) regulations into the industrial organization approach to banking and analyze the interaction between capital adequacy regulation and credit risk transfer with credit default swaps (CDS) including its effect on lending behavior and risk sensitivity of a risk-neutral bank. CDS contracts may be used to hedge a bank's credit risk exposure at a certain (potentially distorted) price. Regulation is found to induce the risk-neutral bank to behave in a more risk-sensitive way: Compared to a situation without regulation the optimal volume of loans decreases more as the riskiness of loansincreases. CDS trading is found to interact with the former effect when regulation accepts CDS as an instrument to mitigate credit risk. Under the substitution approach in Basel II (and III) a risk-neutral bank will over-, fully or under-hedge its total exposure to credit risk conditional on the CDS price being downward biased, unbiased or upward biased. However, the substitution approach weakens the tendency to over-hedge or under-hedge when CDS markets are biased. This promotes the intention of the Basel II (and III) regulations to 'strengthen the soundness and stability of banks'.
Keywords: G21; G28; 330; Banking; regulation; credit risk; Bank; Kreditgeschäft; Kreditrisiko; Basel II; Credit Default Swap; Theorie